TRAINING IN MAKING SOYA MILK TO INCREASE THE ENTREPRENEURIAL MOTIVATION OF SEKOLAH INDONESIA JEDDAH (SIJ) STUDENTS - Miranti, Mauren; Dwi Indriyanti, Aries; Suparji; Maspiyah; Handajani, Sri (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
In an increasingly competitive era, students need to be equipped not only with formal education, but also practical skills that can support their independence in the future. One skill that is relevant and has economic value is the ability to produce products that have market prospects, such as soya milk. The purpose of writing this research is to find out how the training process of making soymilk and calculating the selling price, and how the participants respond to the training activities. The methods used were lectures, questions and answers and demonstrations. The results showed 1) the implementation of the training began with the provision of basic materials related to soymilk processing, and then the practice of making soymilk together. Before the training, participants were given a pre-test first. The pre-test provided an overview of the extent of participants' understanding or skills before starting the program. There was an increase in understanding from before and after the training, and 2) in the participants' response to the activities, in general the participants responded well, all indicators were generally in the good and excellent categories. With this training, students are expected to not only be able to produce quality soymilk, but also have the motivation and confidence to try small business opportunities.